Creating a high-performing school management team: bringing talent to the table for effective service delivery - Klinck, Kezell; Thutulwa, Nancy; Pelser, Anna-Marie (Frontiers in Education, 2023)
The primary goal of this article is to help members of School Management Teams (SMT) in developing their abilities, which will lead to successful service delivery in secondary schools. The study used a qualitative research technique with an exploratory research design with a structured interview questionnaire to determine if SMTs had certain competences, knowledge, or attributes that increase their abilities and to provide recommendations for enhanced service delivery. The research enlisted the help of n = 12 participants from four different secondary schools to get first-hand experience of the phenomena under inquiry. Participants were specifically picked for their expertise, knowledge, and talents. Data were collected from participants via interviews, and the data were evaluated using content analysis. Atlas-ti (Version 8.2) was used to evaluate data collected from participants. The researcher used a qualitative research approach, namely a phenomenological strategy based on constructivism. With no data modification, this technique was adopted to understand the viewpoints of the SMT inside the selected schools. According to the research results, SMTs have competences, knowledge, and characteristics that increase their abilities, and strengthening these talents leads to efficient service delivery. Leadership, communication, collaboration, and problem-solving abilities were among the talents assessed. Understanding school legislation and regulations, curriculum creation, and teaching strategies were all part of the expertise. Among the characteristics were flexibility, resilience, inventiveness, and enthusiasm. The research advises that SMTs be provided opportunity to develop their abilities via training and mentoring programs based on the results. Several of the duties that School Management Teams (SMTs) are in charge of include procuring teaching and learning resources, updating physical buildings, coordinating community support for funding, and utilizing communication channels. The provision of inclusive learning support in schools is strongly related to these responsibilities. The study determined a certain set of talents and characteristics needed by SMTs, such as interpersonal skills, managerial skills, emotional intelligence, effective communication, and team-building skills. These qualities are essential for SMTs to carry out their duties and contribute to better service delivery. The future improvement of service delivery focus on three critical areas: strengthening academic performance, advancing social justice education, and raising student achievement. It is recommended that, by addressing these issues, service delivery within the educational system will be considerably improved in the future.